HUBUNGAN INTENSITAS PENERANGAN, MASA KERJA DAN LAMA KERJA DENGAN KETAJAMAN PENGLIHATAN - Agus Suherman; Ulfa Nurullita (Jurnal Kesehatan Masyarakat Indonesia, 2015)
Background: Lighting in the workplace is necessary for workers especially for jobs that require precision, but if lighting in the work place is bad it will affect the visual acuity. The factors that cause visual acuity are such as age, length of employment, years of employment, light intensity, medications, illness, vitamin A, contrast. Luminensi Objectives: To investigate the relationship illumination intensity, long service life and working with visual acuity. Methods: This type of the analytic is an observational research with cross sectional approach. The independent variable is the intensity of illumination, long service life and work and the dependent variable is visual acuity. The sample of the research is the traditional weavers of workers belonging to Mr. Haji Usman and Ansor in Wanarejan village, Taman district, Pemalang regency consists of 40 people. Statistical analysis is Chi-square test. Results: Most of the intensity of illumination in the workplace including the bad category are 34 persons (85,5%), length of employment > 3 years were 29 persons (72,5%), and respondents working time ? 8 hours / days as many as 33 persons (82, 5%) and abnormal sharpness respondents were 35 persons (87,5%), whereas the normal 5 persons (12,5%).. Conclusion: There is a significant correlation between the intensity of illumination with visual acuity in the traditional weavers (p = 0,018), there is no significant correlation between long working life and working with visual acuity in the traditional weavers with values respectively (p = 1,000) and (p = 0,565).